Frequency and Predictors of Traumatic Encephalopathy Syndrome in a Prospective Cohort of Retired Professional Athletes - Schaffert, Jeff; Didehbani, Nyaz; LoBue, Christian; Hart, John; Rossetti, Heidi; Lacritz, Laura; Cullum, C. Munro (Frontiers in Neurology, 2021)
Traumatic encephalopathy syndrome (TES) is proposed to represent the long-term impact of repetitive head-injury exposure and the clinical manifestation of chronic traumatic encephalopathy (CTE). This study aimed to evaluate the frequency of TES in a cohort of retired professional contact sport athletes, compare the frequency of TES to clinical consensus diagnoses, and identify predictors that increase the likelihood of TES diagnosis. Participants were 85 retired professional contact sport athletes from a prospective cohort at the University of Texas Southwestern Medical Center and the University of Texas at Dallas. Participants ranged in age from 23 to 79 (M = 55.95, SD = 13.82) and obtained 7 to 19 years of education (M = 16.08, SD = 1.03). Retirees were either non-Hispanic white (n = 62) or African-American (n = 23). Retired athletes underwent a standard clinical evaluation, which included a clinical interview, neurological exam, neuroimaging, neuropsychological testing, and consensus diagnosis of normal, mild cognitive impairment, or dementia. TES criteria were applied to all 85 athletes, and frequencies of diagnoses were compared. Fourteen predictors of TES diagnosis were evaluated using binary logistic regressions, and included demographic, neuropsychological, depression symptoms, and head-injury exposure variables. A high frequency (56%) of TES was observed among this cohort of retired athletes, but 54% of those meeting criteria for TES were diagnosed as cognitively normal via consensus diagnosis. Games played in the National Football League (OR = 0.993, p = 0.087), number of concussions (OR = 1.020, p = 0.532), number of concussions with loss of consciousness (OR = 1.141 p = 0.188), and years playing professionally (OR = 0.976, p = 0.627) were not associated with TES diagnosis. Degree of depressive symptomatology, as measured by the total score on the Beck Depression Inventory-II, was the only predictor of TES diagnosis (OR = 1.297, p < 0.001). Our results add to previous findings underscoring the risk for false positive diagnosis, highlight the limitations of the TES criteria in clinical and research settings, and question the relationship between TES and head-injury exposure. Future research is needed to examine depression in retired professional athletes.